Seismic Demand on Column Splices in Steel Moment Frames - Shen, Jay; Sabol, Thomas A.; Akbas, Bulent; Sutchiewcharn, Narathip (Engineering Journal, 2010)
This study addresses seismic demands on column splices in steel moment-resisting frames. A comprehensive nonlinear analytic investigation was undertaken to evaluate the seismic response analysis of 4-, 9- and 20-story moment-resisting frames subjected to an ensemble of 20 strong ground motions. The outcomes of the study include an analysis of the comprehensive seismic demand on the column splice and recommended guidelines for design requirements for reliable moment frame column splices. The study concludes that the demand on the column splice can approach the nominal design strength of the smaller column when the critical beam-to-column connection reaches its expected maximum deformation capacity. It is reasonable that seismic design provisions for the column splices in special and intermediate moment frames require the column splice to develop the fl exural strength of the smaller column.